👤

Bonjour pourriez vous m'aider ? Il faut développer...
3x (x + 1) + 2x
(x + 7) (x - 2)
(5x + 6) (2x - 1)
(x + 2) (x - 5) + (x - 3) (x + 4)
3 (x - a) + a (3 - x) + x (a - 3)
(x - 6) (x + 1) - (x + 6) (x - 1)

mercii


Répondre :

Développer puis réduire.a=3x (x + 1) + 2x
a= 3x²+3x+2x
a= 3x²+5x

b=(x + 7) (x - 2)
b=x²+7x-2x-14
b= x²+5x-14

c= (5x + 6) (2x - 1)
c= 10x²+12x-5x-6
c= 10x²+7x-6

d=(x + 2) (x - 5) + (x - 3) (x + 4)
d= x²+2x-5x-10+x²-3x+4x-12
d= 2x²-2x-22

e=3 (x - a) + a (3 - x) + x (a - 3)
e= 3x-3a+3a-ax+ax-3x
e=0

f=(x - 6) (x + 1) - (x + 6) (x - 1)
f= x²-6x+x-6 - (x²+6x-x-6)
f= x²-5x-6 - (x²+5x-6)
f= x²-5x-6-x²-5x+6
f= -10x
Bonjour,

3x (x + 1) + 2x
= 3x² + 3x + 2x
= 3x² + 5x

(x + 7) (x - 2)
= x² - 2x + 7x - 14
= x² + 5x - 14

(5x + 6) (2x - 1)
= 10x² - 5x + 12x - 6
= 10x² + 7x - 6

(x + 2) (x - 5) + (x - 3) (x + 4)
= x² - 5x + 2x - 10 + x² + 4x - 3x - 12
= x² + x² - 5x - 3x + 2x + 4x - 10 - 12
= 2x² - 8x + 6x - 22
= 2x² - 2x - 22

3 (x - a) + a (3 - x) + x (a - 3) 
= 3x - 3a + 3a - ax + ax - 3x
= 3x - 3x - 3a + 3a - ax + ax
= 0

(x - 6) (x + 1) - (x + 6) (x - 1)
= x² + x - 6x - 6 - (x² - x + 6x - 6)
= x² + x - 6x - 6 - x² + x - 6x + 6
= x² - x² + x + x - 6x - 6x - 6 + 6
= 2x - 12x 
= - 10x